Natural History, Neuroradiological Workup, and Management Options of Chronic Atlantoaxial Rotatory Fixation Caused by Drug-Induced Cervical Dystonia. (3rd March 2021) - Ishikawa, Yuki; Kato, So; Ganau, Mario; Hirai, Shima; Oshima, Yasushi; Tanaka, Sakae
Abstract : Atlantoaxial rotatory fixation (AARF) resulting from drug-induced cervical dystonia (DICD) represents an extremely rare complication of antipsychotic treatment, requiring a comprehensive assessment of pharmacologic therapy and timely radiologic workup. We report a chronic case of Fielding type I, Pang type I AARF secondary to schizophrenia treatment in a 16-year-old girl, along with a review of the literature on the management challenges posed in this condition. In this scenario, torticollis may just represent the tip of the iceberg, and only an effective multidisciplinary approach increases the chances of satisfactory correction with closed reduction, hence avoiding the burden of more invasive treatment options.